The Ionian Bank : an Imperial Institution, 1839-1864 - Cottrell, Philip L., 1944- (Alpha Bank Historical Archives, 2007)
[…] This volume considers the bank’s first quarter of a century, a period when the Ionian Islands, the centre of its operations, continued to be a British protectorate.